Recommendations for cognitive screening and management in multiple sclerosis care - Kalb, Rosalind; Beier, Meghan; Benedict, Ralph Hb; Charvet, Leigh; Costello, Kathleen; Feinstein, Anthony; Gingold, Jeffrey; Goverover, Yael; Halper, June; Harris, Colleen; Kostich, Lori; Krupp, Lauren; et al. (Multiple sclerosis, 2018)
To promote understanding of cognitive impairment in multiple sclerosis (MS), recommend optimal screening, monitoring, and treatment strategies, and address barriers to optimal management. The National MS Society ("Society") convened experts in cognitive dysfunction (clinicians, researchers, and lay people with MS) to review the published literature, reach consensus on optimal strategies for screening, monitoring, and treating cognitive changes, and propose strategies to address barriers to optimal care. Based on current evidence, the Society makes the following recommendations, endorsed by the Consortium of Multiple Sclerosis Centers and the International Multiple Sclerosis Cognition Society: Increased professional and patient awareness/education about the prevalence, impact, and appropriate management of cognitive symptoms. For adults and children (8+ years of age) with clinical or magnetic resonance imaging (MRI) evidence of neurologic damage consistent with MS: As a minimum, early baseline screening with the Symbol Digit Modalities Test (SDMT) or similarly validated test, when the patient is clinically stable; Annual re-assessment with the same instrument, or more often as needed to (1) detect acute disease activity; (2) assess for treatment effects (e.g. starting/changing a disease-modifying therapy) or for relapse recovery; (3) evaluate progression of cognitive impairment; and/or (4) screen for new-onset cognitive problems. For adults (18+ years): more comprehensive assessment for anyone who tests positive on initial cognitive screening or demonstrates significant cognitive decline, especially if there are concerns about comorbidities or the individual is applying for disability due to cognitive impairment. For children (<18 years): neuropsychological evaluation for any unexplained change in school functioning (academic or behavioral). Remedial interventions/accommodations for adults and children to improve functioning at home, work, or school.